Explaining focal points: Cognitive hierarchy theory versus team reasoning - Nicholas Bardsley; Judith Mehta; Chris Starmer; Robert Sugden (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2008)
This paper reports experimental tests of two alternative explanations of how players use focal points to select equilibria in one-shot coordination games. Cognitive hierarchy theory explains coordination as the result of common beliefs about players' pre-reflective inclinations towards the relevant strategies; the theory of team reasoning explains it as the result of the players' using a non-standard form of reasoning. We report two experiments. One finds strong support for team reasoning; the other supports cognitive hierarchy theory. In the light of additional questionnaire evidence, we conclude that players' reasoning is sensitive to the decision context.
Keywords: C72; C92; 330; salience; focal point; cognitive hierarchy; team reasoning; Spieltheorie; Kognition